Neutron Scattering to Characterize Cu/Mg(Li) Destabilized Hydrogen Storage Materials - M. H. Braga (2010)
Cu-Li-Mg-(H,D) was studied as an example of destabilizer of the Ti-(H,D) system. A Cu-Li-Mg alloy was prepared resulting in the formation of a system with 60.5 at% of CuLi0.08Mg1.92, 23.9 at% of CuMg 2 and 15.6 at% of Cu2Mg. Titanium was added to a fraction of this mixture so that 68.2 at% (47.3 wt%) of the final mixture was Ti. The mixture was ground and kept at 200 °C/473 K for 7h under H2 or 9h under D2 at P = 34 bar. Under those conditions, neutron powder diffraction shows the formation of TiD2, as well as of the deuteride of CuLi0.08Mg1.92. Similarly inelastic neutron scattering shows that at 10 K TiH2 is present in the sample, together with the hydride of CuLi0.08Mg1.92. Interestingly, at 10 K TiH 2 is very clearly detected and at 300 K TiH2 is still clearly present as indicated by the neutron vibrational spectrum, but CuLi 0.08Mg1.92-H is not detected anymore. These results indicate that Ti(H,D)2 is possibly formed by diffusion of hydrogen from the Cu-Li-Mg-(H,D) alloys. This is an intriguing result since TiH 2 is normally synthesized from the metal at T > 400°C/673 K (and most commonly at T ∼ 700 °C/973 K). In the presence of CuLi 0.08Mg1.92, TiH2 forms at a temperature that is 300 - 400 K lower than that needed to synthesize it just from the elements.